When liberty presupposes order: F. A. Hayek's learning ordoliberalism - Stefan Kolev (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2021)
This paper contextualizes the early political economy of Austrian economist and social philosopher F. A. Hayek in the intellectual milieu of German ordoliberalism. It argues that the particular urgency during the 1930s and 1940s to preserve and stabilize the disintegrating orders of economy and society was a crucial driver behind the numerous parallelisms between Hayek and the ordoliberals. Their political economies are reconstructed by emphasizing the notion of the framework as an economic constitution of general and stable rules, with the overarching goal to render the orders in the postwar world more robust. In a nutshell, the central configuration is that liberty can thrive sustainably only after such a framework has been established. Hayek's "learning ordoliberalism" emerged during the socialist calculation debates when knowledge became the center of his oeuvre, so that he aimed at identifying rules which could enhance the use of knowledge in society and thus societal learning. Hayek's search was similar to that of the ordoliberals in substance and in rhetoric, and culminated in the competitive order as the chiffre for a well-ordered market economy. These parallelisms surfaced during the 1930s and became most explicit in The Road to Serfdom and at the founding meeting of the Mont Pèlerin Society in 1947. In the years after The Constitution of Liberty, a shift of Hayek's focus is identified: from a theory of designing frameworks at a point of time towards a theory of their evolution across time. Overall, Hayek of the 1930s and 1940s is interpreted as a continental liberal thinking in interdependent societal orders, while the ordoliberals are depicted as a constitutive building block of the international neoliberal archipelago.
Keywords: A11; B25; B31; B41; H11; P16; 330; neoliberalism; ordoliberalism; Freiburg School; F. A. Hayek; Walter Eucken; Wilhelm Röpke